2011
DOI: 10.1089/end.2010.0431
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Radiation Exposure with the Use of an Air Retrograde Pyelogram During Fluoroscopic Access for Percutaneous Nephrolithotomy

Abstract: An air retrograde pyelogram is associated with decreased radiation exposure during PNL when compared with a contrast retrograde pyelogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The median BMI of our study population is within the reported range in our geographic area 23 and is comparable to similar PCNL studies reporting BMI. 15,19,20,24 The mean fluoroscopy time in our study cohort was only 3.4 minutes, which is shorter than most case series using standard PCNL techniques (Table 4), and the mean effective dose of 2.4 mSv in our cohort compares favourably to published reports. For standard PCNL using contrast pyelography, Lipkin and colleagues 24 reported a mean fluoroscopy time about 3 times the amount in our study cohort.…”
Section: Tion Exceed the International Commission On Radiologicalsupporting
confidence: 64%
See 1 more Smart Citation
“…The median BMI of our study population is within the reported range in our geographic area 23 and is comparable to similar PCNL studies reporting BMI. 15,19,20,24 The mean fluoroscopy time in our study cohort was only 3.4 minutes, which is shorter than most case series using standard PCNL techniques (Table 4), and the mean effective dose of 2.4 mSv in our cohort compares favourably to published reports. For standard PCNL using contrast pyelography, Lipkin and colleagues 24 reported a mean fluoroscopy time about 3 times the amount in our study cohort.…”
Section: Tion Exceed the International Commission On Radiologicalsupporting
confidence: 64%
“…15,19,20,24 The mean fluoroscopy time in our study cohort was only 3.4 minutes, which is shorter than most case series using standard PCNL techniques (Table 4), and the mean effective dose of 2.4 mSv in our cohort compares favourably to published reports. For standard PCNL using contrast pyelography, Lipkin and colleagues 24 reported a mean fluoroscopy time about 3 times the amount in our study cohort. In 2010, Mancini and colleagues 19 reported a retrospective review of 96 cases of standard PCNL.…”
Section: Tion Exceed the International Commission On Radiologicalsupporting
confidence: 64%
“…A retrospective review of 92 patients in which PCNL access was achieved with the use of air nephrograms rather than with iodinated contrast showed an approximately 50% reduction in radiation exposure. 16 As with obese patients, the mechanism for this is from the increased voltage of the C-arm to compensate for the dense contrast in comparison with the surrounding tissue. Data on the use of ureteroscopic guided PCNL puncture has been presented with relatively low STs and radiation exposure-4.2 minutes and 2.8 mSv, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the present study was to identify clinical, imaging and intraoperative parameters that increase FT during PCNL in order to enhance our knowledge on this 65% and 35% decrease in FT, respectively [21,22]. The implementation of a reduced fluoroscopy protocol was associated with an 80% decrease in FT [3].…”
Section: Discussionmentioning
confidence: 90%